Knowledge on integrated management of childhood illness among health and family planning field workers (Asian Journal of Medical and Biological Research, 2021)
Integrated Management of Childhood illness (IMCI) is a strategy for reducing mortality among children under the age of 5 years. This study was aim to assess the level of knowledge on IMCI among health and family planning field worker. Convenience sampling and a semi-structured questionnaire was used to collect data among 237 respondents. Knowledge level was categorised as good, average and poor while association of categorical data were done by Chi squire test. The mean age of participants was 36.03±10.13 years where (82.3%) respondents were female. The mean duration of job was 11.27± 9.81 years where (71.7%) respondents did not have training on IMCI. Among the respondents, 42.6% didn’t know any of the objectives and 46.8% respondents knew that one of the components of IMCI, 51.5% respondents knew that IMCI to improve the health system and 35.3% respondents knew that IMCI is to improve family and community practice. Signs of diarrhoea in 0-2 month’s old baby was not known by 27.8% respondents. Majority of the respondents (72.2%) had knowledge about increased respiratory rate as a sign of pneumonia. Among the respondents, 42.6% respondents had poor knowledge regarding IMCI while 28.7% had well and (28.7%) had average knowledge. Level of knowledge was significantly associated with age (p